2019
DOI: 10.3390/foods8120642
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Noble Rot Infection of Garganega Withered Grapes with Key Molecules and Odorants of Botrytized Passito Wine

Abstract: Experimental passito wines with different percentages of naturally noble-rotten grapes of the Garganega variety were analyzed to evaluate key molecules and odorants related to the typical aroma and sensory profile of botrytized passito wine. Remarkable changes in the concentration of 1-octen-3-ol, 4-terpineol, benzaldehyde, N-(3-methylbutyl)acetamide, and sherry lactone 1 and 2 were observed between sound and noble-rotten wines. Wines were perceived to be different for floral, honey, figs, apricot, and caramel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…The literature concerning sparkling wines is mainly related to Valdobbiadene (VAL_BRU; VAL_EXD) [ 67 ] and Recioto Spumante Metodo Classico (REC) wines [ 68 ] and is consistent with the results obtained in the present study. Recioto Spumante Metodo Classico (REC), a typical Italian sweet wine, was mainly characterised by a caramel odour and the macrocategories of nuts and dried fruits.…”
Section: Discussionsupporting
confidence: 92%
“…The literature concerning sparkling wines is mainly related to Valdobbiadene (VAL_BRU; VAL_EXD) [ 67 ] and Recioto Spumante Metodo Classico (REC) wines [ 68 ] and is consistent with the results obtained in the present study. Recioto Spumante Metodo Classico (REC), a typical Italian sweet wine, was mainly characterised by a caramel odour and the macrocategories of nuts and dried fruits.…”
Section: Discussionsupporting
confidence: 92%
“…Both 1-octen-3-ol and 1-octen-3-one were also found in Riesling, Gewurztraminer [ 12 ], Merlot, Gamay, Semillon and Cabernet Sauvignon musts affected by Botrytis cinerea , the gray rot pathogen, and Penicillium brevicompactum [ 7 ]. In the case of musts affected by Botrytis cinerea , the associated Fiano wines contain a concentration of 1-octen-3-ol that increases with the percentage of rotten grapes [ 13 ]. Recently, it was demonstrated that Crustomyces subabruptus was able to release 1-octen-3-one in both contaminated musts and wines under laboratory conditions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aroma compounds are particularly relevant in Passito wines and are strongly influenced by vineyard practices, noble rot presence, grape characteristics, and dehydration conditions [3,4,[24][25][26][27], as well as winemaking technology and evolution [2,28,29]. In particular, using cv Muscat of Alexandria, the relationship between grape volatile content and wine quality is dependent on the terpene content and profile.…”
Section: Introductionmentioning
confidence: 99%